Stimulation of the L2–L3 Dorsal Root Ganglia Induces Effective Pain Relief in the Low Back. Issue 2 (6th December 2017) - Huygen, Frank; Liem, Liong; Cusack, William; Kramer, Jeffery
Abstract: Introduction: Chronic low back pain affects millions of people worldwide and can arise through a variety of clinical origins. In the case of failed back surgery syndrome (FBSS), previous surgical procedures can contribute to low back pain that is often unresponsive to intervention. Although spinal cord stimulation (SCS) can be an effective treatment modality, it does not provide sufficient pain relief for some intractable cases. Recently, alternative neuromodulation options have been developed, including dorsal root ganglion (DRG) stimulation. The objective of this report is to further investigate these clinical observations. Methods: Twelve patients with significant chronic discogenic low back pain due to FBSS were included. All subjects underwent implantation of DRG stimulation systems that had at least 1 lead placed at L2 or L3. Subjects' pain ratings, mood, and quality of life were tracked prospectively for up to 12 months. Results: More than half of subjects reported 50% or better pain relief in the low back, and the average low back pain relief was 45.5% at 12 months. Concomitant reductions in overall pain, leg pain, pain interference, mood, and quality of life were also found. Discussion: For the studied population, DRG stimulation at the L2–L3 levels was effective at relieving low back pain. These reductions in pain were associated with improvements in quality of life. Thus, DRG stimulation at these levels may be effective for low back pain by recruiting both segmental and nonsegmental neural pathways that are not otherwise accessible via traditional SCS.